Overcoming Regional Disparities in Serbia through Regional Innovation Systems at the NUTS II Level - Ivanič, Valentina (Észak-magyarországi Stratégiai Füzetek, 2023)
The objective of this research is to reveal and understand the strengths and weaknesses of the two groups of regional innovation systems in Serbia – those operating in Belgrade and Vojvodina region, with strong administrative capacity, and those operating in Šumadija and Western Serbia and Southern and Eastern Serbia, operating without administrative capacity at the regional level. Data were collected from existing databases, and interviews with members of the focus groups. The action research methodology was used also. The findings show that regions without administrative capacity have RDAs with cooperative culture, more externally oriented, and more devoted to building eonomic software and economic orgware axis instead of the regions with administrative capacity. The mature RIS is present in the regions without administrative power in Serbia (Šumadija and Western Serbia, Southern and Eastern Serbia) in comparison to two NUTS II regions (Belgrade and Vojvodina region)